PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA KARYAWAN PT. APLIKANUSA LINTAS ARTA PEKANBARU - Riswanda, Dedi; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to determine the effect of education and training on the performance of employees of PT. Aplikanusa Lintasarta Pekanbaru. This study uses a questionnaire as a data collection tool that is distributed to 29 employees of PT. Aplikanusa Lintasarta Pekanbaru. Data from the questionnaire were further processed using descriptive analysis and statistical analysis using SPSS 25 by conducting validity, reliability testing, simple linear analysis, coefficient of determination analysis, and hypothesis testing consisting of t test (partial).       The results of this study indicate that the results of the first hypothesis testing namely education and training on employee performance shows t arithmetic (2.509)> t table (2.09302), meaning that education and training affect employee performance. Keywords: Education and Training, Employee Performance